High Efficient Metadevices for Terahertz Beam Shaping - Li, Xinan; Shen, Zhixiong; Tan, Qinggui; Hu, Wei (Frontiers in Physics, 2021)
Metasurfaces supply a planar approach for flexible wavefront manipulation, thus facilitating the integration and minimization of optical elements, especially in the terahertz (THz) range. High efficient THz metadevices are highly pursued at present. Here, we propose a bilayer design to improve the efficiency of metadevice. Two silicon pillar arrays with distinguished geometries are integrated on single silicon substrate. On one side, elliptical silicon pillars, with geometry optimized for the target frequency, are spatially orientated to realize the desired Pancharatnam-Berry phase. On the other side, uniform circular silicon pillars are set to suppress the reflection. With this design, versatile metadevices such as lens, lens array, polarization fork grating, Bessel vortex generator and Airy beam generator are demonstrated. High efficiency up to 95% for objective frequency and excellent design flexibility are verified. It provides a practical strategy for the generation of compact and high efficient THz metadevices, which suit for high-performance THz imaging and communication apparatuses.